IMPACT OF LEADERSHIP STYLES ON EMPLOYEE PERROMANCE: A REVIEW OF LITERATURE - Raveendran, T.; Gamage, A.S (University of Jaffna, 2018)
The business researchers are interested in identifying what leadership styles result in positive outcomes in organizations. From the work of the researchers, many theories and approaches have been developed time to time. This paper provides a literature review of transformational and transactional leadership styles and its impact on employee performance. The review outlines the major leadership theories and provides a framework for understanding the body of knowledge. Transformational and transactional leadership theories are discussed in detail in order to provide a specific leadership theoretical framework for this study. Empirical findings related to the study variables are discussed based on the literature. The review of literature shows that the leaders are perceived effective when they use transformational and transactional leadership styles together. Further several studies identified that, compared to transactional leadership, transformational leadership has more impact on employee performance. However, there is a gap in the current literature examining the effects of transformational and transactional leadership styles on employee performance in the Sri Lankan context. The review results would bring a platform for the future researchers to concentrate on the applicability of the theory in various sectors in Sri Lanka.
Keywords: transformational leadership; transactional leadership; employee performance